Diphenylphosphino Styrene‐Containing Homopolymers: Influence of Alkylation and Mobile Anions on Physical Properties. Issue 14 (27th May 2016) - Jangu, Chainika; Schultz, Alison R.; Wall, Candace E.; Esker, Alan R.; Long, Timothy E.
Abstract : Conventional free radical polymerization and post‐alkylation of 4‐diphenylphosphino styrene (DPPS) generate a new class of high‐molecular‐weight phosphonium‐containing homopolymers with tunable thermal, viscoelastic, and wetting properties. Post‐alkylation and subsequent anion exchange provide an effective method for tuning T g values and thermal stability as a function of alkyl chain length and counteranion selection (X −, BF4 −, TfO −, and Tf2 N − ). Rheological characterization facilitates the generation of time–temperature–superposition (TTS) pseudomaster curves and subsequent analysis of frequency sweeps at various temperatures reveals two relaxation modes corresponding to long‐range segmental motion and the onset of viscous flow. Contact angle measurements reveal the influence of counteranion selection on wetting properties, revealing increased contact angles for homopolymers containing nucleophilic counteranions. These investigations provide fundamental insight into phosphonium‐containing polymers, aiming to guide future research and applications involving electro‐active polymeric devices. Abstract : Conventional free radical polymerization and post‐alkylation of 4‐diphenylphosphino styrene achieve a new class of high‐molecular‐weight phosphonium‐containing homopolymers with tunable thermal, viscoelastic, and wetting properties. Post‐alkylation and subsequent anion exchange provide an effective method for tuning T g values and thermal stability as a function of alkyl chain length and counteranion selection.